2014
DOI: 10.1186/2050-6511-15-13
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional investigation of the quality of selected medicines in Cambodia in 2010

Abstract: BackgroundAccess to good-quality medicines in many countries is largely hindered by the rampant circulation of spurious/falsely labeled/falsified/counterfeit (SFFC) and substandard medicines. In 2006, the Ministry of Health of Cambodia, in collaboration with Kanazawa University, Japan, initiated a project to combat SFFC medicines.MethodsTo assess the quality of medicines and prevalence of SFFC medicines among selected products, a cross-sectional survey was carried out in Cambodia. Cefixime, omeprazole, co-trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
5
22
0
Order By: Relevance
“…In the case of OM, at least 33.8% of samples failed the DS in the acid phase and/or buffer phase. This is similar to the high failure ratio in DS of OM samples collected in the Cambodian pharmaceutical market [ 4 , 22 ]. The cause of this high DS failure ratio of OM in Myanmar should be investigated.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In the case of OM, at least 33.8% of samples failed the DS in the acid phase and/or buffer phase. This is similar to the high failure ratio in DS of OM samples collected in the Cambodian pharmaceutical market [ 4 , 22 ]. The cause of this high DS failure ratio of OM in Myanmar should be investigated.…”
Section: Discussionsupporting
confidence: 71%
“…We have been attempting to clarify distribution channels of such poor-quality medicines, and to check the spread of such medicines. Although the World Health Organization (WHO) reported that the proportion of substandard or counterfeit drugs supplied in developed countries was approximately 1% [ 3 ], the risks appear to be increasing according to the development of the Internet and the progress of globalization [ 4 ]. WHO also reported that the proportion of such poor-quality drugs supplied in developing countries was about 10% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this study is the potential desirability effect: community members and HCPs may have answered in a way that they believed made their views more favourable to researchers or other participants. It is likely that IMS are found more frequently in rural areas,50 and our results may underestimate the presence of and reliance on IMS. Future studies in rural Cambodia may provide an insightful comparison with our results.…”
Section: Discussionmentioning
confidence: 69%
“…In 2015, 128 countries were impacted by pharmaceutical crime, including sale of substandard and falsified medicines (SFs), and the number of incidents in the Asia Pacific Region exceeded 1,000 for the first time. [1][2][3][4][5][6][7][8][9] The World Health Organization and the European Commission have warned about the danger posed to public health by SFs, and pointed out the need for measures to detect and prevent distribution of SFs. [10][11][12] The term of falsified medicines means any medicinal product with a false representation of 1) its identity, including packaging, labeling, name, or composition, as regard any of the ingredients including excipients and the strength of those ingredients; 2) its source, including manufacturer, country of manufacture, country of origin, or marketing authorization holder; or 3) its history, including records and documents relating to the distribution channels used.…”
Section: Introductionmentioning
confidence: 99%